The mighty Thor : an origin story - Thomas, Rich; Storybook Art Group (New York : Marvel, 2013)
Tells the story of Thor, prince and great protector of Asgard, whose father Odin strips him of his memory and power and banishes him to Earth to learn humility, the only virtue he lacks, so that he might wield the mighty hammer Mjolnir.
Reprint. Originally published: c2011.
"Based on the Marvel comic book series Thor."
Keywords: Thor (Norse deity) -- Fiction; Superheroes -- Fiction; Humility -- Fiction; Thor (Norse deity) -- Fiction; Superheroes -- Fiction; Humility -- Fiction